Remote banking: the essence and current state of implementation in the Ukrainian banking market. - Харабара, Віолетта; Грешко, Роман Ігорович (My University, 2024)
The article examines the issue of providing various services to customers remotely by banks. Today, in the modern world, banking is one of the most favorable areas for the introduction and development of information technology. Therefore, the theoretical aspects of remote banking and Ukraine's place among European countries in the ranking of Internet banking usage were studied. The constant increase in competition in this sector pushes for the inevitable improvement of banking services, i.e. the search for the latest and highest quality communication with customers. That is why the most popular services among Internet banking users were reviewed and highlighted. The state of remote banking in Ukraine is analyzed, namely, the share of transactions using electronic means of payment issued by Ukrainian banks, the distribution of non-cash transactions using payment cards by their number and amount. The advantages and reasons for slowing down the development of remote banking services were also presented.
Keywords: remote banking service; internet banking; mobile banking; banking services; cashless payments